Pengaruh Atraksi dan Harga Tiket terhadap Minat Kunjung Ulang ke Trans Studio Mini Malang - Setiawan, Friska Aldi; Estikowati, Estikowati; Alvianna, Stella; Lasarudin, Alwin (University of Merdeka Malang, 2023)
Trans Studio Mini Malang is one of the attractions in the city of Malang with an attraction that has a selling point, followed by interesting attractions, then affordable prices. This will make Trans Studio Mini Malang a tourist attraction that is good for the community to make repeat visits. this study aims to determine the effect of attractions and ticket prices on interest in repeat visits to Trans Studi Mini Malang, this type of research is quantitative with the method used is multiple linear regression with the help of the SPSS25 programme. Data collection techniques by distributing questionnaires to visitors who have visited Trans Studio Mini Malang, a total of 53 respondents. The results of the study partially showed that tourist attractions had an effect X1: 0.223 in re-visit interest, while ticket prices had a significant effect X2: 0.785 on tourists' re-visit interest to Trans Studio Mini Malang with the total amount. So it is hoped that the ticket price at Trans Studio Mini Malang can be considered by the manager. The conclusion that can be drawn is that the ticket price is the biggest influence on tourist re-visit interest to Trans Studio Mini Malang.